(3GdHjGf aj Gdabgs - (3jMji Hf CHj GdNjQ Hf eMeO Hf ehSi GdYeQGfj SGde Hf SYjO Hf YHO Gddgs
(3ChdgG (B:s
(3cJGH GdfabGJ , HGH fabg GdRhLGJ s
(3BNQgG (B:s
(3BNQg ef (B" (3HGH LGeY GdEbQGQ (B" (3bhdg (B: (3hcGfJ LGQjI Ydi eG KHJ dgG ef MQeI GdESJjdGO , hGdhdO Ydi eGKHJ dg ef GdMQjI , hGddg CYde HGdUhGH , Je GdcJGH s
(3cJHJ HYV GdYfGhjjf HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3Gdabg GdTGaYjs